ANALISIS KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH PADA BANK JATENG CABANG PEMBANTU SAMPANGAN - Ardhila Laela Kusumastuti; M Abdul Kodir (KEUNIS, 2019)
This study aims to determine and measure the effect of Service Quality variables on Customer Loyalty at Bank Jateng Branch of Sampangan. The data in this research is obtained by filling the questionnaire to 100 customers of Bank Jateng Sampangan Branch Office. Sampling using purposive sampling method while data testing method is done by Test Validity, Test Reliability, Classic Assumption Test, t test, F test, and Coefficient of Determination. Data analysis method used is multiple linear regression analysis with SPSS program version 24. The result of testing the hypothesis indicate that there are significant effects both simultally and partislly on service quality variable to customer loyalty at Bank Jateng Sampangan Branch Office and variable of Reliability is dominant variable that influence to customer loyalty at Bank Jateng Branch of Sampangan.